Efforts by Unit IV Satintelkam Through Early Detection for the Prevention of Motor Vehicle Theft Crimes in Sukoharjo Police Resort (Indonesian Journal of Police Studies, 2024)
Motor vehicle theft is a rampant form of crime in the jurisdiction of the Sukoharjo Police Resort. The crime of motorcycle theft can be prevented through early detection by the Intelligence Unit of the Sukoharjo Police Resort to create public order. The purpose of this final project is to describe the system of the Unit IV method of the Intelligence Unit of the Sukoharjo Police Resort and crime prevention through early detection for the prevention of motorcycle theft. This research is qualitative in nature with a field research approach. Data was obtained through in-depth interviews, observation, and document study. The theories and concepts used are the management function theory and crime prevention theory, effort concept, intelligence unit concept, early detection concept, crime prevention concept, and motorcycle theft concept. The results of the study show that the system of the Unit IV method of the Intelligence Unit of the Sukoharjo Police Resort and crime prevention through early detection for the prevention of motorcycle theft is not in line with relevant police regulations, theories, and concepts. Additionally, internal and external factors that support or do not support early detection through the prevention of motorcycle theft have led to suboptimal results. Therefore, the Head of Unit IV of the Intelligence Unit of the Sukoharjo Police Resort, as the subject of this final project, needs to take problemsolving measures.
Keywords: DETEKSI DINI; TINDAK PIDANA; SATUAN INTELKAM